2020
DOI: 10.1186/s12887-020-02120-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of clinical training on improving essential newborn care practices in Bossaso, Somalia: a pre and postintervention study

Abstract: Background: Increasingly, neonatal mortality is concentrated in settings of conflict and political instability. To promote evidence-based practices, an interagency collaboration developed the Newborn Health in Humanitarian Settings: Field Guide. The essential newborn care component of the Field Guide was operationalized with the use of an intervention package encompassing the training of health workers, newborn kit provisions and the installation of a newborn register. Methods: We conducted a quasi-experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 20 publications
0
50
0
Order By: Relevance
“…Our results are consistent with those of Bang et al and Drake et al who documented that ongoing training programmes are more effective and necessitated, as these can improve knowledge and skill retention, especially in resource-limited countries ( 22 , 27 ). A pre- and post-intervention study testing a long-term newborn training programme in Somalia over a two-and-a-half-year period (including an 18-month follow-up) demonstrated that some skills did not improve ( 28 ). Issues such as hand hygiene and discharge education did not improve over time, and the authors suggested that different training approaches were needed to address the local needs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those of Bang et al and Drake et al who documented that ongoing training programmes are more effective and necessitated, as these can improve knowledge and skill retention, especially in resource-limited countries ( 22 , 27 ). A pre- and post-intervention study testing a long-term newborn training programme in Somalia over a two-and-a-half-year period (including an 18-month follow-up) demonstrated that some skills did not improve ( 28 ). Issues such as hand hygiene and discharge education did not improve over time, and the authors suggested that different training approaches were needed to address the local needs.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is congruent with the previous studies [ 5 , 17 ]. This can be explained by healthcare providers who took essential newborn care training or courses that can ensure the skills and knowledge to provide up-to-date evidence-based information and management for a range of needs in the initial newborn period [ 22 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early rooming-in and skin-to-skin within 1 hour of life after birth provides optimal thermal care, encourages breastfeeding, enhances bonding and good for mother's wellbeing as it helps control intrapartum bleeding. 5,[9][10][11]…”
Section: Thermal Care Practicesmentioning
confidence: 99%
“…Dry cord care is recommended, however in high mortality settings, chlorhexidine is recommended. 6,[9][10][11] exclusive breastfeeding for 6 months. Breastfeeding should be continued with safe complementary foods after 6 months.…”
Section: Hygienic Cord Carementioning
confidence: 99%